Modulation of the Hoffmann reflex in the tibialis anterior with a change in posture. Issue 14 (17th July 2019) - Unger, Janelle; Andrushko, Justin W.; Oates, Alison R.; Renshaw, Doug W.; Barss, Trevor S.; Zehr, E. Paul; Farthing, Jonathan P.
Abstract: Hoffmann (H‐) reflex amplitudes in plantar flexor soleus muscle are modulated by posture, yet dorsiflexor tibialis anterior (TA) H‐reflex parameters have sparingly been studied. The purpose was to investigate modulation of the TA H‐reflex when postural demands are increased from sitting to standing. In this study, data from 18 participants (Age: 25 ± 4 years, Height: 170.9 ± 9.5 cm, Weight: 75.9 ± 17.2 kg) allowed comparison of two experimental conditions involving different postures (i.e. sitting and standing). Maximal amplitude of the TA H‐reflex ( H max ) as a percent of the maximal M‐wave amplitude ( M max ) ( H max (% M max )) during sitting and standing was compared using ANOVA. Modulation of TA H‐reflex amplitude was found: Eleven participants showed facilitation and seven showed no change of reflex amplitudes. Only participants in the facilitation group showed modulation related to changes in posture (sitting: 8.7 ± 2.9%; standing: 14.8 ± 6.7%, P = 0.005). These data provide evidence of the sensitivity to posture of TA H‐reflexes. As with task‐dependent changes in soleus H‐reflexes, presynaptic regulation of Ia afferent transmission is a possible mechanism. Further investigations into causes of modulation are warranted. Abstract : The Hoffmann reflex was found to modulate differently for individuals with a change in postural demand.